A Japanese patient with RAD51‐associated Fanconi anemia. Issue 6 (25th March 2019) - Takenaka, Satoshi; Kuroda, Yukiko; Ohta, Sayaka; Mizuno, Yoko; Hiwatari, Mitsuteru; Miyatake, Satoko; Matsumoto, Naomichi; Oka, Akira
Abstract: RAD51 is the only identified autosomal dominant gene to date causative of Fanconi anemia (FA) due to dominant negative effects. Only two patients with RAD51‐associated FA have been reported with atypical FA phenotypes without bone marrow failure. We describe a new Asian patient with a novel RAD51 mutation, presenting with multiple congenital anomalies and atypical FA with chromosomal instability. The patient was a 9‐year‐old Japanese girl. She had strabismus, myopia, submucous cleft palate, bilateral hearing impairment, and scoliosis. She also had growth retardation, developmental delay, and severe intellectual disability. We performed trio whole exome sequencing and Sanger sequencing and identified a de novo RAD51 mutation (c.725A>G, p.Gln242Arg). Isolated lymphocytes from the patient were hypersensitive to chromosomal breakage induced by the DNA cross‐linking agent, mitomycin C. Our detailed phenotypic analysis of the RAD51 ‐associated atypical FA revealed clinical manifestations from the diverse population and a consistent FA phenotype characterized by chromosome instability, intellectual disability, radial ray abnormality, and microcephaly, but not bone marrow failure.